2022
DOI: 10.1038/s41598-022-04919-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and behavior of incarcerated people regarding COVID-19 and related vaccination: a survey in Italy

Abstract: The cross-sectional study assessed knowledge, attitudes, and preventive practices toward COVID-19 disease of incarcerated people. A total of 685 subjects were surveyed. 94% were aware that respiratory droplets are involved in the transmission of COVID-19, and 77.2% that patients with chronic conditions are at risk of a more severe disease. Overall, 92.7% of respondents considered COVID-19 a more severe disease compared to influenza, and 85.4% believed that COVID-19 could cause serious consequences in their ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In other words, participants who expressed not wanting a COVID-19 vaccine perceived themselves at relatively low risk of a severe SARS-CoV-2 infection. Other studies have confirmed similar findings; younger incarcerated people were less likely to accept a COVID-19 vaccine [33] , [34] , [36] , [37] , [38] , [39] . Conversely, older participants with concomitant comorbidities expressed a greater interest in vaccination, recognizing their heightened risk of severe disease.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In other words, participants who expressed not wanting a COVID-19 vaccine perceived themselves at relatively low risk of a severe SARS-CoV-2 infection. Other studies have confirmed similar findings; younger incarcerated people were less likely to accept a COVID-19 vaccine [33] , [34] , [36] , [37] , [38] , [39] . Conversely, older participants with concomitant comorbidities expressed a greater interest in vaccination, recognizing their heightened risk of severe disease.…”
Section: Discussionsupporting
confidence: 69%
“…Participants reported that COVID-19 vaccine information was insufficient and incomplete, and acknowledged that inadequate information could impact vaccine hesitancy. Previous studies in correctional facilities also demonstrated that people who fail to acknowledge the severity of the disease [39] or who have concerns regarding side effects and suboptimal vaccine efficacy [33] are more likely to decline COVID-19 vaccination. While providing adapted information will be key, addressing misinformation such as conspiracies to harm will be equally important as misinformation has been shown to be associated with reduced vaccination intent [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns surrounding side effects and efficacy were major reasons for hesitancy, reflecting findings from other studies in the US and abroad ( Stern et al, 2020 , Aw et al, 2021 , Tyson, 2020 , Solís Arce et al, 2021 , Di Giuseppe et al, 2022 ). Although guidance for booster shots had not yet emerged during the study period, many respondents--especially vaccine hesitant respondents--indicated that needing an annual booster would be a deterrent to vaccination.…”
Section: Discussionmentioning
confidence: 74%
“…This survey was carried out between July and October 2021, within a larger project developed by the University of Campania “Luigi Vanvitelli” and the Joint Operational Unit for Health Protection at Prison Institutions, investigating several health-related issues in the incarcerated population [ 21 , 23 , 24 ]. Three prisons in the geographic area of Campania region, in the South of Italy, were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Since monitoring of vaccine knowledge, attitudes, and behaviors has been placed as a strategic basis for all vaccination programs [ 18 ], and the study of the determinants of vaccination choice as one of the guiding tools for national immunization programs and for the development of specific strategies for the improvement of coverage [ 18 ], several studies have been conducted to explore the willingness of people in prison to undergo COVID-19 vaccination, as well as determinants of intention to uptake the vaccine [ 19 , 20 , 21 ]. However, despite the contribution of studies on willingness and related determinants is undoubtedly relevant, it is known that intention to undergo vaccination may not always predict real vaccination uptake [ 22 ], and identification of determinants of hesitancy among those who delay or refuse vaccinations is a key component in the design of interventions aimed at the achievement of successful vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%